Amalgamation of the North China Craton: Key issues and discussion - Zhao, G.; Cawood, P.; Li, S.; Wilde, Simon; Sun, M.; Zhang, J.; He, Y.; Yin, C. (Elsevier BV, 2012)
Geological and geophysical data indicate that the Precambrian basement of the North China Craton (NCC) formed by amalgamation of a number of micro-continental blocks. The number of blocks, when they existed and how they came together are controversial, and in particular the following issues are disputed: (1) the timing of collisional event(s) leading to the amalgamation of the Eastern and Western blocks along the Trans-North China Orogen (TNCO); (2) the polarity of the subduction between the Eastern and Western blocks; (3) the validity of an old continental block (Fuping Block) that collided with the Eastern Block at ~2.1 Ga; (4) the tectonic setting of the northern margin of the NCC in the Paleoproterozoic; (5) the tectonic nature of high-pressure (HP) and ultrahigh temperature (UHT) granulite-facies events in the Khondalite Belt of the Western Block; and (6) the tectonic setting of the Paleoproterozoic Jiao-Liao-Ji Belt in the Eastern Block.Analysis and integration of available stratigraphic, structural, geochemical, metamorphic and geochronologic data enable the development of an internally consistent and coherent model for assembly and stabilization of the various Archean blocks of the NCC in the Paleoproterozoic. All metamorphic ages obtained for the TNCO are around 1.85 Ga, which establishes that the final amalgamation of the Western and Eastern blocks of the craton occurred at ~1.85 Ga. The TNCO is characterized by a fan-shaped pattern of structural features, with the top-to-the-NW and top-to-the-SE thrusting in the northwest and southeast, respectively. This pattern does not constrain subduction polarity for the collisional assembly of the Eastern and Western blocks. Structures in lithospheric mantle and asthenosphere in the TNCO have been significantly modified/replaced in the Mesozoic and Cenozoic, and hence the present-day orientation of these structures, even if they relate to Paleoproterozoic assembly of the craton cannot be used to infer associated subduction polarity.There are no unique structural data or available metamorphic data to supporting the existence of an old continental block that intervened between the Eastern and Western Blocks, which collided with the Eastern Block at ~2.1 Ga. Available data are also inconsistent with the existence of the Paleoproterozoic Inner Mongolia-North Hebei Orogen along the northern margin of the NCC that formed through accretion of an exotic arc at ~2.3 Ga and incorporated into the PaleoproterozoicColumbia (Nuna) Supercontinent at 1.92–1.85 Ga. We interpret the north Hebei portion of this inferredorogen as part of the TNCO, and the Inner Mongolian portion as an independent continental block (Yinshan Block). This block is separated from the Ordos Block by the Paleoproterozoic Khondalite Belt. The high-/medium-pressure granulite facies metamorphic event in the Khondalite Belt is considered to have resulted from collision between the Yinshan and Ordos blocks to form the Western Block at ~1.95 Ga, whereas the ~1.92 Ga UHT metamorphism within the belt was related to the underplating or intrusion of mantle-derived magmas during the post-collisional extension. The Jiao-Liao-Ji Belt in the Eastern Block likely formed through Paleoproterozoic rifting to form the Longgang and Langrim blocks, and subsequent basin closure and collision in the period 2.2–1.9 Ga.